Inclusive agricultural transformation: Strengthening farmer–research–extension linkage platforms and digital feedback for a responsive innovation system in Ethiopia - Girmay, Eyuel; Mesfin, Tewodros; Tolosa, Debbebe; Abera, Wuletawu; Erkossa, Teklu; Degefie, Tibebe; Desta, Lulseged; Ebrahim, Mohammed; Assefa, Feben; Kihara, Job (2026)
Ethiopia’s agricultural extension system is transitioning from a traditional, top-down technology transfer model toward a more inclusive, responsive, and data-driven innovation approach. This blog highlights how the Farmer–Research–Extension (FRE) linkage platform, combined with a digital Client Feedback Mechanism (CFM), is transforming the way agricultural solutions are co-designed, delivered, and continuously refined. By creating regular spaces for dialogue among farmers, extension agents, researchers, and local institutions, the FRE platform ensures that farmers’ priorities and field realities directly inform research agendas and extension responses. The digital feedback tool strengthens this process by capturing geo-referenced, real-time information on emerging challenges and integrating it into national data systems, enabling faster coordination and more timely responses across administrative levels. Piloted across multiple districts, the initiative has directly benefited smallholder farmers—including women and youth—extension agents, district experts, and researchers. More than 480 geo-referenced farm plots have received site-specific fertilizer and lime advisories, with early adoption exceeding 15%, reflecting growing trust in and relevance of the recommendations. Key outcomes include greater farmer participation in decision-making, more locally tailored advisory services, faster institutional responses to production constraints, and stronger coordination between research and extension systems. While challenges remain related to financing, digital inclusion, and access to inputs, the FRE–CFM model demonstrates a practical and scalable pathway for building a farmer-centered, adaptive agricultural innovation system in Ethiopia, with lessons applicable to other contexts.